Analysis of 5 Floor Brick Masonry Building, Type 77/5 (European Journal of Formal Sciences and Engineering, 2025)
This study investigates the seismic performance and structural improvement of a five-floor Type 77/5 brick masonry building through both linear and nonlinear analysis methods. The research employs finite element modeling using ETABS software for linear analysis and AM-Quake for nonlinear analysis to evaluate building performance against Eurocode standards. Initial findings revealed critical vulnerabilities, including excessive displacement (12.91 cm versus the allowable 7.1 cm) and periods of oscillation (0.688 sec versus the recommended 0.366 sec). Multiple reinforcement strategies were systematically tested, including concrete cladding, full concrete wall replacement, and fiber-glass reinforcement, with limited success. The study ultimately demonstrates that selective column implementation in the first two floors provides the most effective and economically viable solution, reducing displacement to 42.19 mm in the plastic phase and bringing the period within acceptable parameters. These findings have particular relevance in the context of Albania's seismic activity, as evidenced by the 6.3 Richter magnitude earthquake of November 26, 2019, and offer practical solutions for similar masonry structures requiring seismic reinforcement in regions with limited economic resources.
Keywords: analysis, 5 floor brick, masonry building, type 77/5